The Effectiveness of a Cognitive Counseling Program in Reducing Cognitive Distortions among Al-Quds Open University Students - Tamoni, Abed Alrhman; Shaheen, Mohammad Ahmed (Dirasat: Educational Sciences, 2021)
This study aims to recognize the effectiveness of a cognitive counseling program in decreasing the cognitive distortions among Al-Quds Open University students, through a sample of 30 students (males and females), who record high degrees of cognitive distortions, divides equally between experimental and control groups. The counseling program is applied to the experimental group, in 12 sessions, one session weekly, each for 90 minutes. The study results show statistically significant differences between the experimental and control groups in the post-measurement on the cognitive distortions, in favor of the experimental group. Differences between the pre and post-measurement in the experimental group are also statistically significant, in favor of the post-measurement. Additionally, there are no statistical differences between the post and long term measurements. The results show that the impact of the counseling program is 0.871 for the post-measurement of cognitive distortions. Based on the results, the study recommends further studies on other societies, based on cognitive theory and aimed at reducing cognitive distortions.